Step-Index Plastic Optical Fibre (SI-POF) Channel Optimisation: M-PAM and Equalization (FULafia Journal of Science and Technology, 2020)
Step-Index Plastic Optical Fibre (SI-POF) is gaining popularity in local area network installations due to its characteristics as an inexpensive medium. This research optimized SI-POF channel of two distances (30metres and 60metres) by introduction of equalizer(s) at the output channel signal with M-PAM (PAM-2 and PAM-4) modulation scheme to address bandwidth limitation and inter symbol interference (ISI). The study which was carried out in MATLAB R2019a environment, study employed decision feedback equalizer-DFE (2, 1), (4, 2) and linear equalizer-LE (2, 0) algorithms to train the output channel signal. The study adopted scatter plots, bit error rate (BER) and data rate (DR) as indices to improve the performance of the output signal.